2014
DOI: 10.1007/s12035-014-9041-x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Neurobiology of Demyelination

Abstract: Despite a large amount of research which aims at defining the pathophysiology of human demyelination (i.e., multiple sclerosis), etiological bases of disease have been unknown so far. The point of intersection of all assumed etiological factors, which are mainly based upon immunological cascades, is neuroinflammation. The precise definition of the place and role of all pathogenetic factors in the occurrence and development of the disease is of crucial importance for understanding the clinical nature and for fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 193 publications
0
38
0
Order By: Relevance
“…It is possible that a new target of treatment will focus on neutralizing free radicals. The course of the disease is affected by the use of antioxidants and substances that affect antioxidant pathways which reduce the severity and cause faster remission and less pronounced course of neuroinflammation and neurodegeneration [76, 91]. …”
Section: The Importance Of Antioxidants In Msmentioning
confidence: 99%
“…It is possible that a new target of treatment will focus on neutralizing free radicals. The course of the disease is affected by the use of antioxidants and substances that affect antioxidant pathways which reduce the severity and cause faster remission and less pronounced course of neuroinflammation and neurodegeneration [76, 91]. …”
Section: The Importance Of Antioxidants In Msmentioning
confidence: 99%
“…These results indicate that while oxidized lipids may not feature in the initial activation of immune cells, they may well play a central role in the subsequent demyelination, as previously suggested. 45 Since oxidized lipoproteins are neurotoxic and have proinflammatory properties, lipid peroxidation products could be involved in demyelination and axonal injury in MS. 46,47 In addition, the activity of Nano-PSO, at least at the particle size shown to be beneficial for EAE, may be mostly confined to the CNS, thereby interfering with brain oxidation features and demyelination and less with inhibition of infiltration. Owing to the lack of toxicity of these reagents, Nano-PSO may be a good choice for individuals at initial stages of demyelinating diseases such as MS. At later stages, Nano-PSO may be used in combination with advanced MS treatments such as Natalizumab (Tysabri), which reduces the migration of lymphocytes to the CNS by binding to the α4 integrin very late antigen, 48 or in combination of other antioxidant formulations.…”
mentioning
confidence: 99%
“…Aside from MtD, OS plays a role in demyelination and axonal damage in MS . Findings from several studies have suggested that OS plays the most important role in the demyelination and neurodegeneration observed in MS . OS causes selective oligodendrocyte death and can disrupt the process of oligodendrocyte differentiation, leading to demyelination .…”
Section: Elucidation Of the Role Of Oxidative Stress (Os) And Mitochomentioning
confidence: 99%
“…34 Also, MtD has been found to play a key role in a progressive axonal loss in MS. 17,35,36 Following axonal demyelination in MS, it has been hypothesized that mitochondria play a greater role in maintaining axonal function as an adaptive process to the increased energy need of demyelinated axons but MtD results over time leading to severe and chronic axonal damage. 35,37,38 F I G U R E 1 The role of mitochondria dysfunction and oxidative stress in MS | 307 TOBORE Aside from MtD, OS plays a role in demyelination and axonal damage in MS. [39][40][41][42] Findings from several studies have suggested that OS plays the most important role in the demyelination and neurodegeneration observed in MS. [42][43][44][45][46] OS causes selective oligodendrocyte death and can disrupt the process of oligodendrocyte differentiation, leading to demyelination. 47,48 Damage from OS on oligodendrocytes and neurons has been found to be associated with active demyelination and axonal or neuronal damage in MS. 42 Studies have revealed that OS modulates OPC signal processes which are vital for OPC proliferation and differentiation resulting in hypomyelination.…”
Section: Neurodegeneration Demyelination and Axonal Loss In Msmentioning
confidence: 99%